Methylation of the glucocorticoid receptor gene promoter in bulimic women: Associations with borderline personality disorder, suicidality, and exposure to childhood abuse. Issue 3 (17th February 2013) - Steiger, Howard; Labonté, Benoit; Groleau, Patricia; Turecki, Gustavo; Israel, Mimi
Abstract: Objective: To compare levels of methylation of the glucocorticoid receptor (GR) gene (NR3C1) promoter between women with bulimia nervosa (BN) and women with no eating disorder (ED), and also to explore, in women with BN, the extent to which methylation of the GR gene promoter corresponds to childhood abuse, suicidality, or borderline personality disorder (BPD). Method: We measured methylation levels in selected NR3C1 promoter regions using DNA obtained from lymphocytes in 64 women with BN (32 selected as having a history of severe childhood abuse and 32 selected as having no such history) and 32 comparison women with no ED or history of childhood abuse. Results: Compared to noneating disordered women, women with BN and comorbid BPD (or BN with a history of suicidality) showed significantly more methylation of specific exon 1C sites. There was also a (nonsignificant) result indicative of greater methylation in some 1C sites among women with BN, when compared (as a group) to women with no ED. No parallel effects owing to childhood abuse were observed. Discussion: Our findings associate BN (when accompanied by BPD or suicidality) with hypermethylation of certain GR exon 1C promoter sites. We discuss theoretical and clinical implications of our findings. © 2013 by Wiley Periodicals, Inc. (Int J Eat Disord 2013)